Acculturation of Indian and Chinese Cultures on Pis Bolong Bali - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2022)
Kamasan, a village in the Klungkung regency, Bali, not only gains its popularity from classical painting. The Village is also widely noticeable for its metallurgy business, especially Pis Bolong Industry. In other areas, the coin is referred to as Uang Kepeng. Historically, the existence of Pis Bolong or holed coin in Bali was brought by Chinese traders between the eighth to fifteen centuries. It has been circulating as a currency for at least 1,100 years. Today, in Bali, Pis Bolong consists of Pancadatu, combining several elements such as Gold, silver, copper, zinc, and iron. The coin plays an important role in Hindu religious activities entrenched in Balinese society. However, since the supply of old holed coins cannot fulfill the demand of Balinese ceremonies today, The Government of Bali decided to reproduce the holed coin. It is viewed as a solution to preserve Pis Bolong's existence despite the currency no longer serving as a payment method. Through the Bali Heritage Trust, the officer made the standardized version of the new Pis Bolong, which is suggested to consist of the Pancadatu element. The first pioneer of Pancadatu-based Pis Bolong manufacture is UD. Kamasan, one of the home-industry businesses from Klungkung that supplies the needs of Pis Bolong on the island. Creativity in creating Pis Bolong handicraft products, in addition to elevating the current value of Pis Bolong, also acts as an effort of cultural preservation that reflects the local wisdom of the Balinese people.